DEVELOPMENT OF SODIUM ALGINATE COATED NANOPARTICLES OF METRONIDAZOLE FOR THE TREATMENT OF PERIODONTITIS - SINGH, MUKUL; JAIN, GAURAV (International Journal of Applied Pharmaceutics, 2019)
Objective: The present study was aimed to develop metronidazole (MNZ) loaded poly lactic-co-glycolic acid (PLGA) based mucoadhesive nanoparticles (NPs) in prolonged treatment in periodontitis. Methods: Nanoparticles were prepared by using single (SE) and double (DE) emulsion method to determine the suitability of methods. Prepared NPs were evaluated for surface morpholgy, mean particle size, polydispersity index, zeta potential, mucoadhesion ability and invitro-drug release, Results: SEM images confirmed that NPs were of spherical shape and smooth surface. Mean particle size, of MNZ loaded NPs were found 583.28±18.22 and 872.72±63.18 prepared by SE and DE method. Similarly, polidispersity index (0.68±0.1 and 0.83±0.06) and zeta potention (-33.29±0.7 and-31.28.0.6) was found in acceptable range. Prepared NPs were surface treated with Sodium alginate (SA) to increase mucoadhesive property. It was observe that particles remain adhere till 24 hr with biological membrane. Prepared NPs allow release of MNZ upto 24 h in sustained manner. Conclusion: This study confirms that the prepared MNZ loaded NPs may be used as an better alternate with addition application such as prolonged action thus improved patient compliance.